Analisis Faktor-Faktor Yang Dapat Meningkatkan Pendapatan Petani Kopi - Klara Sinta, Shela; Nusantoro, Jawoto; Febri Darmayanti, Elmira (Universitas Muhammadiyah Metro, 2025)
This study is research that uses a qualitative approach with qualitative descriptive methods, aiming to analyze factors that have the potential to increase the income of coffee farmers in Kubuliku Jaya Village, Batu Ketulis District, West Lampung Regency. The population that was the subject of this research was 633 respondents, with a sample of 86 respondents using the Slovin formula with a significance level of 10%. The data analysis process includes data reduction, data presentation and verification stages, as well as testing the validity of the data through credibility tests, dependability tests, transferability tests and confirmability tests. The data analysis tool used is the Guttmann scale. The research results show that factors such as processing technology, production yields, land productivity, and climate change have a significant impact on the income of coffee farmers in Kubuliku Jaya Village, Batu Ketulis District, West Lampung Regency.